Alzheimer's Disease and Mild Cognitive Impairment - Jones, David T; Bruns, Marla B; Petersen, Ronald C (The Wiley Handbook on the Aging Mind and Brain, 2018)
Research on the pathophysiology of Alzheimer's disease (AD) has indicated that there is an element of inflammation involved in the degenerative process. Since this element of inflammation may influence the progression of the disease and hence the symptoms, several studies have been undertaken to determine the possible efficacy of anti‐inflammatories in treating AD. Atypical clinical presentations of AD occur with initial prominent symptoms in visual‐spatial abilities, language, or executive functioning. However, these are much less common than the typical memory‐predominate presentation. Neuropsychological testing can help determine if the subject is experiencing cognitive changes of normal aging or the earliest signs of AD or possibly mild cognitive impairment (MCI). In general, atypical antipsychotic medications are preferred in the treatment of psychosis in AD because of a better side effect profile. Implicit in a discussion of AD and MCI is knowledge about cognitive changes in normal aging.